Improving quality of life for Muslim patients requiring a stoma: A critical review of theological and psychosocial issues. Issue 1 (20th January 2020) - Habib, Abul; Connor, Martin J.; Boxall, Nicholas E.; Lamb, Benjamin W.; Miah, Saiful
Abstract: Aim: The impact of a stoma on the health related quality of life (HRQoL) in patients is irrespective of faith. Muslim patients report lower quality of life and spiritual well‐being following stoma surgery as compared to others. This critical review aims to improve awareness of Islamic practices and HRQoL outcomes in this cohort of patients amongst healthcare professionals. Method: An extensive non‐systematic search of EMBASE, MEDLINE and Google Scholar was performed for original research articles pertaining to health related quality of life (HRQoL), stoma care and impact on religious practice in Muslim patients. A narrative synthesis of extracted data was performed and presented using basic thematic analysis. Results: The findings from the 10 original articles, including 954 participants, were identified. Perceptions of cleanliness emerged as a concern to Muslim patients with stomas as it is core to the performance of prayer. Muslim patients with stomas are known to avoid or reduce participation in prayers due to perceived inferior hygiene and fear of leakage. The consensus opinion from Islamic scholars is that they can pray normally, attend mosque and perform the Hajj pilgrimage. Stoma patients may fast in the holy month of Ramadan provided it is medically safe. Evidence suggests religion‐specific counselling can reduce the detrimental effect on HRQoL of Muslim patients following stoma‐forming surgery and increases engagement in social aspects of life. Conclusions: It is important for patients, family members and healthcare professionals to understand the practical and religious implications of stomas on these patients for appropriate guidance and counselling.